«Fue levado mi entendimiento»: Teresa de Cartagena y la escritura mística en femenino. - TIMONER, Mª MAR CORTÉS (Scripta, 2016)
Around the years 1470-1475, the nun Teresa de Cartagena (niece of the renowned humanist Alfonso de Cartagena) wanted and needed to write about her personal female experience of God's love, and left us two valuable treatises that open the path to the writings composed by 16th-century Castilian nuns. Teresa stands out meritoriously in the history of late medieval literature and she can be considered a worthy precursor of the great Teresa de Jesús. Both women writers share certain biographical and spiritual similarities that deserve to be taken into account when designing a genealogy of female authors of spiritual literature in Spanish.